PELAKSANAAN PEMEKARAN DESA OENITAS, KECAMATAN ROTE BARAT, KABUPATEN ROTE NDAO DI TINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Lifu, Fikto Chrisfalsa; Udju, Hernimus Ratu; Lamataro, Cyrilius W T (Petitum Law Journal, 2024)
Based on the author's observations, the background to the main problem can be formulated as to what extent the conditions for implementing Village expansion and what are the influencing factors, the implementation of Village expansion is related to the expansion of Oenitas village, West Rote District, Rote Ndao Regency. The purpose of this research is to find out and analyze the implementation of village expansion and identify factors inhibiting the implementation of village expansion in Oenitas Village, West Rote Ndao Regency, Rote District. This research is based on primary, secondary, and tertiary data using an empirical juridical approach, and it was carried out using the Qualitative Descriptive Analysis Method in accordance with the data obtained while still paying attention to theories, principles, and legal rules in order to address this problem. The study's findings demonstrate that when implementing Village expansion, the Village requirements are in accordance with the stages, namely the requirements consist of population size, territorial boundaries, and infrastructure. the existence of tug-of-war interests between communities and the lack of natural resources, human resources (HR).